Odpowiedź:
1)[tex]3\sqrt{7} =\sqrt{3^2*7} =\sqrt{9*7}=\sqrt{63}[/tex]
[tex]4\sqrt{3}=\sqrt{4^2*3} =\sqrt{16*3} =\sqrt{48}[/tex]
2)[tex]\sqrt{75} =\sqrt{25*3} =5\sqrt{3}[/tex]
3)a)[tex]\sqrt{18} -2\sqrt{8} +3\sqrt{50} =3\sqrt{2} -2*2\sqrt{2} +3*5\sqrt{2} =3\sqrt{2} -4\sqrt{2} +15\sqrt{2} =14\sqrt{2}[/tex]
b)[tex]\sqrt{24} :\sqrt{\frac{3}{2} } =\sqrt{24*\frac{2}{3} } =\sqrt{8*2} =4[/tex]
c)[tex]\sqrt[3]{2\frac{10}{27} } =\sqrt[3]{\frac{64}{27} } =\frac{4}{3} =1\frac{1}{3}[/tex]
d)[tex]\sqrt[3]{729} -\sqrt[3]{-343} =9-(-7)=9+7=16[/tex]
e)[tex]\sqrt[3]{14^2-13^2} =\sqrt[3]{196-169} =\sqrt[3]{27} =3[/tex]
Szczegółowe wyjaśnienie: